Using Expressive Writing in Helping Learning Difficulty Problems: Systematic Literature Review - Tririzky, Reza; Afdal, Afdal; Ifdil, Ifdil; Marjohan, Marjohan; Ardi, Zadrian (International Journal of Applied Counseling and Social Sciences, 2024)
Expressive writing activities are one of the approaches that can be an alternative in helping to solve the problems of learning difficulties faced by students. In order to gain a better understanding of this, it is necessary to conduct a study to understand the extent of the usefulness of expressive writing activities. The purpose of this study is to review the application of expressive writing activities in helping to solve learning difficulties. Furthermore, systematic literature review research was applied using the PRISMA method to fulfill the research objectives. Data collection was done through digital tracking from a reliable source, Google Scholar. After the tracking and selection process, 11 studies were collected that discussed expressive writing activities and learning difficulties. It was found that expressive writing is one of the alternative activities to help solve various learning difficulties.